Heterodimeric BMP‐2/7 for nucleus pulposus regeneration—In vitro and ex vivo studies. Issue 1 (7th July 2016) - Li, Zhen; Lang, Gernot; Karfeld‐Sulzer, Lindsay S.; Mader, Kerstin T.; Richards, R. Geoff; Weber, Franz E.; Sammon, Chris; Sacks, Hagit; Yayon, Avner; Alini, Mauro; Grad, Sibylle
ABSTRACT: Intervertebral disc (IVD) degeneration is the leading trigger of low back pain, which causes disability and leads to enormous healthcare toll worldwide. Biological treatment with growth factors has evolved as potential therapy for IVD regeneration. Bone morphogenetic protein 2 (BMP‐2) and BMP‐7 have shown promise in this regard. In the current study, we evaluated the effect of BMP‐2/7 heterodimer for disc regeneration both in vitro and in organ culture. Nucleus pulposus (NP) cells isolated from bovine caudal disc were cultured in a fibrin‐hyaluronan (FBG‐HA) hydrogel for up to 14 days. BMP‐2/7 heterodimer covalently incorporated within the hydrogel up‐regulated the aggrecan and type II collagen gene expression, and glycosaminoglycan synthesis of NP cells. The activity of the BMP‐2/7 heterodimer was dose dependent. The higher dose of BMP‐2/7 was further assessed in an IVD whole organ system. After 14 days of culture with cyclic dynamic load, the BMP‐2/7 heterodimer delivered into the nucleotomized region showed potential to stimulate the gene expression and synthesis of proteoglycan in the remaining NP tissue after partial nucleotomy. The gene expression level of type I collagen and alkaline phosphatase in the native disc tissue were not affected by BMP‐2/7 treatment, indicating no adverse fibroblastic or osteogenic effect on the disc tissue. Intradiscal delivery of BMP‐2/7 heterodimer may be a promising therapeutic approach for NP regeneration. The current IVD whole organ partial nucleotomy model may be utilized for screening of other biomaterials or drugs to treat early degenerative disc disorders. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:51–60, 2017.